RepD-mediated recruitment of PcrA helicase at the Staphylococcus aureus pC221 plasmid replication origin, oriD - Machόn, Cristina; Thomson, N.H.; Lynch, G.P.; Scott, David J.; Thomas, C.D.; Soultanas, Panos (Oxford Journals, 2010)
Plasmid encoded replication initiation (Rep) proteins recruit host helicases to plasmid replication origins. Previously, we showed that RepD recruits directionally the PcrA helicase to the pC221 oriD, remains associated with it, and increases its processivity during plasmid unwinding. Here we show that RepD forms a complex extending upstream and downstream of the core oriD. Binding of RepD causes remodelling of a region upstream from the core oriD forming a 'landing pad' for the PcrA. PcrA is recruited by this extended RepD-DNA complex via an interaction with RepD at this upstream site. PcrA appears to have weak affinity for this region even in the absence of RepD. Upon binding of ADPNP (non-hydrolysable analogue of ATP), by PcrA, a conformational rearrangement of the RepD-PcrA-ATP initiation complex confines it strictly within the boundaries of the core oriD. We conclude that RepD-mediated recruitment of PcrA at oriD is a three step process. First, an extended RepD-oriD complex includes a region upstream from the core oriD; second, the PcrA is recruited to this upstream region and thirdly upon ATP-binding PcrA relocates within the core oriD.